2019
DOI: 10.1111/acer.14218
|View full text |Cite
|
Sign up to set email alerts
|

Social Desirability Bias Impacts Self‐Reported Alcohol Use Among Persons With HIV in Uganda

Abstract: Background: Self-report is widely used to assess alcohol use in research and clinical practice, but may be subject to social desirability bias. We aimed to determine if social desirability impacts self-reported alcohol use.Methods: Among 751 human immunodeficiency virus (HIV)-infected patients from a clinic in southwestern Uganda, we measured social desirability using the Marlowe-Crowne Social Desirability Scale (SDS) Short Form C, self-reported alcohol use (prior 3 months) Alcohol Use Disorders Identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…These associations may have been caused by residual confounding if the level of alcohol consumption was differentially underreported by race/ethnicity. We have observed high social desirability and underreport of alcohol use by Ugandans living with HIV in prior studies (Adong et al, 2019; Bajunirwe et al, 2014; Muyindike et al, 2017) and underreport has also been reported for racial and ethnic minorities compared to whites in the United States (Johnson & Bowman, 2003; White et al, 2014).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…These associations may have been caused by residual confounding if the level of alcohol consumption was differentially underreported by race/ethnicity. We have observed high social desirability and underreport of alcohol use by Ugandans living with HIV in prior studies (Adong et al, 2019; Bajunirwe et al, 2014; Muyindike et al, 2017) and underreport has also been reported for racial and ethnic minorities compared to whites in the United States (Johnson & Bowman, 2003; White et al, 2014).…”
Section: Discussionmentioning
confidence: 49%
“…To do so, we conducted an individual participant data meta‐analysis to leverage the statistical power of multiple studies with PEth testing and self‐reported alcohol use. Since social desirability bias suggests a tendency to underreport alcohol consumption (Adong et al, 2019), we have chosen to evaluate the sensitivity of PEth among those volunteering substantial alcohol consumption, that is, unhealthy alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…First, although the population prevalence of alcohol consumption in this parish is similar to that reported elsewhere in Uganda [9,10], personal alcohol consumption may be under‐reported [101–103]. Research using objective biomarkers to assess consumption levels would be helpful to determine actual population norms for comparison with perceived norms.…”
Section: Discussionmentioning
confidence: 64%
“…Given that the loss to follow‐up was greater in the EUC arm it is possible that the MI‐CBT intervention was more effective than EUC in promoting better engagement in care. Fourth, a limitation of our study is that alcohol use was measured with the AUDIT which is a self‐report questionnaire and subject to social desirability bias [51]. Social desirability may have led to bias in the reporting of reduced alcohol use in the intervention arm.…”
Section: Discussionmentioning
confidence: 99%